Strengthening Nurses’ Understanding And Documentation Practice in EMR-Based Discharge Planning - Rakhmawati, Rani; Ahsan; Samsul Ma’arif (Department of Nursing, Faculty of Health Sciences, Universitas Brawijaya., 2026)
Incomplete documentation and limited nurse understanding of electronic-medical-record-based discharge planning were identified as recurring problems in the inpatient ward of RSI Aisyiyah Malang, increasing the risk of discontinuity of care for patients with chronic conditions and postoperative cases. This community service program aimed to strengthen nurses' understanding and practice of electronic-medical-record-based discharge planning through an implementation approach covering planning, organizing, actuating, and controlling stages over four weeks, involving 26 nurses. Activities included a needs assessment and documentation audit during the planning stage, development of standard procedures, a discharge planning module, and digital educational media during the organizing stage, socialization and procedure reinforcement during the actuating stage, and post-intervention evaluation through documentation audits and checklist assessment during the controlling stage. Nurses' understanding improved across all five measured indicators on a five-point scale, with the largest gain in understanding of the discharge planning workflow (mean 3.8 to 4.3) and the smallest in perceived responsibility for completing discharge planning documentation. Documentation audits of 72 electronic medical records showed 97.2% compliance and 93.2% completeness, while checklist usability evaluation showed a mean score of 4.0 with an 80% achievement rate, reflecting a positive perception of usability and effectiveness. However, technical barriers and interprofessional coordination gaps still affected completeness of patient and family education documentation. These findings indicate that a short-term, structured, nurse-focused intervention can strengthen nurses' understanding and documentation practices in electronic medical record (EMR)- based discharge planning, though sustained supervision and system support are needed to consolidate these gains into consistent long-term practice.